The next phase of business ethics : celebrating 20 years of REIO - Schwartz, Michael; Harris, Howard; Comer, Debra R. (Research in ethical issues in organizations ;, 2019)
The role of organizations in society, the international and multidisciplinary scope of business ethics, and the importance of narrative were concerns that were raised in early volumes of Research in Ethical Issues in Organizations (REIO). That these topics remain of interest is perhaps sobering, and a cause for reflection in the business ethics community. What has the discipline of business ethics achieved over the last 20 years? Where is at in 2019? Where is it headed? Written to celebrate the founding of the series 20 years ago, the volume tackles the tendency to see business as something spawned in recent times. REIO's founders, even in 2001, were contemplating the next phase of business ethics, and saw it linked to both good corporate practice and a multidisciplinary heritage stretching back in time. This volume considers whether scholars, practitioners, and business professionals have been slow to act, or whether the problems are intractable. The role of film and narrative in the development of ethical standards and in business ethics education is addressed. Individual submissions also consider corporate responsibility, redemption, and the nature of boundaries in organizations and personal life.The volume will appeal to academics in the business ethics field and related disciplines.